A simple proof for Euler's formula

Euler's formula: $$e^{i\theta}=\cos \theta + i \sin \theta$$ Let $f(\theta )=e^{i\theta}$ and $g(\theta )= \cos \theta + i \sin \theta$, considering $i$ as a constant, lets make our first contact with the proof we need. For $\theta = 0$,  we see that $f(0) = g(0) = 1$, but this is not enough for saying that both functions are actually equal. Then, we will just make our first derivative of both functions: $$f'(\theta) = e^{i \theta} \cdot \frac{d \left ( i \theta \right )}{d \theta}=e^{i \theta } \cdot i := i \cdot f(\theta)$$ $$g ' (\theta) = -\sin \theta + i \cos \theta = i^2 \sin \theta + i \cos \theta := i \cdot g(\theta)$$ We got the same differential equation for both functions. This means there is gonna be, at first: one general solution that includes both functions. But considering that the point $P(0,1)$ belongs to $f(\theta)$ and $g(\theta)$ at the same time, the constant that appears in the general solution will disappear. In other words, the function t...

Demostración - Incumplimiento de la regla conmutativa (Operaciones Con Matrices)

$$A \cdot B \neq B \cdot A$$
Demostraré la propiedad de forma general:
Teniendo en cuenta las matrices:

$A=\begin{pmatrix}
a & b\\
c & d
\end{pmatrix}, B=\begin{pmatrix}
e & f\\
g & h
\end{pmatrix}$


$A \cdot B=\begin{pmatrix}
a & b\\
c & d
\end{pmatrix} \cdot \begin{pmatrix}
e & f\\
g & h
\end{pmatrix} = \begin{pmatrix}
ae+bg & af+bh \\
ce+dg & cf+dh
\end{pmatrix}$

$B \cdot A=\begin{pmatrix}
e & f\\
g & h
\end{pmatrix} \cdot \begin{pmatrix}
a & b\\
c & d
\end{pmatrix}=\begin{pmatrix}
ea+fc & eb+fd \\
ga+hc & gb+hd
\end{pmatrix}$
$\therefore A \cdot B \neq B \cdot A$

  Existen otras formas de verificar la propiedad: Por ejemplo, podría haber existido el producto de $A \cdot B$, pero no $B \cdot A$. Como por ejemplo:
 
$A=\begin{pmatrix}
3 & 2\\
7 & 1
\end{pmatrix} , B=\begin{pmatrix}
2 & 3 & -1\\
0 & 1 & 2
\end{pmatrix} \rightarrow \begin{matrix}
\exists \: A \cdot B\\ \nexists \: B \cdot A
\end{matrix}$

Por el incumplimiento de esta regla, hemos de especificar el orden de las matrices en un producto. Por ejemplo, para $A \cdot B$; decimos que A está multiplicando a B por la derecha.

Comentarios

Entradas populares de este blog

VALOR ABSOLUTO

POLINOMIO DE TAYLOR

MÉTODO DE NEWTON-RAPHSON